Advertising layout - D.E. Visuals (Firm) (Florida : D.E. visuals, 2006)
Part I demonstrates the uses of the illustration, headline, copy and logo; basic art layout such as line, flow, patterns; and mechanics such as white space and bleed. Part II discusses proportion, design components, arrangement formats, visual direction and visual organization. Also covers visual attention techniques of juxtaposition, spatial progression, overlapping and closure.
DVD format
Keywords: Advertising; Advertising layout and typography; Advertising -- Psychological aspects